3(k+5)=2(3k+6)

Simple and best practice solution for 3(k+5)=2(3k+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(k+5)=2(3k+6) equation:



3(k+5)=2(3k+6)
We move all terms to the left:
3(k+5)-(2(3k+6))=0
We multiply parentheses
3k-(2(3k+6))+15=0
We calculate terms in parentheses: -(2(3k+6)), so:
2(3k+6)
We multiply parentheses
6k+12
Back to the equation:
-(6k+12)
We get rid of parentheses
3k-6k-12+15=0
We add all the numbers together, and all the variables
-3k+3=0
We move all terms containing k to the left, all other terms to the right
-3k=-3
k=-3/-3
k=1

See similar equations:

| t=-13t^2+572t | | 3(5x+10)=5(x+30) | | 9x-7+8x=90 | | 0.4x÷8=0.2x+12.5 | | 4(-p+1)=-4p+4 | | 12w+7=15w-5 | | x+9/2=-1 | | 2(1+4x)=17+5x | | 2(x-7)^2-1=55 | | 19x+15-9x=10+5x-20 | | -0.5x+3.2=7 | | 9x+1=4x-9=0 | | x+43.75=12 | | -19+n/4=-13 | | x^2+115=2x^2+90 | | 3(x-1)+8(x-3)=+7-5x | | 10+3/4x=1/4+13 | | 4(6x+1)+x=5(5x+-1) | | 2-4n=-5-3n | | 9.2r+5.51=158.23r= | | 0.5x+3.2=7 | | 6x+9=9x+15 | | 6m-6=9m+8 | | -3=2k+6-1 | | 2x+x=2x+(2x-3)+(x-1)=76 | | 4.5x-1.8=11.7 | | -13+43=-3(x+3) | | d+7/3=4. | | 6x+3(4x+2)=5(2x-8) | | (3x/4)-(1/2)=7 | | x2-18=82 | | 3(2g+4)=5g+8+3g |

Equations solver categories